2012
DOI: 10.1063/1.3684603
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of intraband absorption in quantum-dot-in-well mid-infrared photodetectors

Abstract: Intraband absorption in quantum-dot-in-a-well (DWELL) mid-infrared photodetectors is investigated using photocurrent spectroscopy and computationally cost-effective modeling linked to experimental data. The DWELL systems are challenging for modeling the electronic structure, which involves both discrete levels and the continuum energy spectrum. We show that the latter can be successfully approximated by a quasi-continuum in a large three-dimensional (3D) “quantum box” in which the electronic structure is calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The intraband absorption spectrum of QDs has been calculated by effective mass approximation. [9][10][11][12] Recently, Luque et al reported that the intraband absorption coefficient for both the bound-to-bound and bound-to-continuum transitions is comparable to the interband absorption coefficient in QDs. 12 On the other hand, the intraband absorption in InAs/ GaAs QDs has been measured by photoinduced absorption spectroscopy 13,14 and time-resolved photoluminescence (PL) quenching measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The intraband absorption spectrum of QDs has been calculated by effective mass approximation. [9][10][11][12] Recently, Luque et al reported that the intraband absorption coefficient for both the bound-to-bound and bound-to-continuum transitions is comparable to the interband absorption coefficient in QDs. 12 On the other hand, the intraband absorption in InAs/ GaAs QDs has been measured by photoinduced absorption spectroscopy 13,14 and time-resolved photoluminescence (PL) quenching measurements.…”
Section: Introductionmentioning
confidence: 99%
“…More modeling formalism details are available in Ref. [4]. Photoluminescence (PL) spectra were measured at 10 K and 300 K using an Ar+-ion laser and a liquid-nitrogen cooled Ge detector.…”
Section: Methods and Approachmentioning
confidence: 99%
“…33 QD intersubband transitions are particularly promising for mid-infrared wavelengths. 34 These transitions allow light emission normal to the growth direction. Additionally, they are a basic requirement for the realization of a QCL consisting of QDs.…”
Section: -20mentioning
confidence: 99%